Proactive Innovation in a Prolonged Conflict Setting: Facing COVID-19 in a Specialized Cancer Hospital in Palestine - Sabateen, Ali; Khalil, Merette; Abu El Hawa, Munia; Peeperkorn, Richard; Mataria, Awad; Ravaghi, Hamid (Frontiers in Public Health, 2022)
The prolonged ongoing conflict in Palestine exacerbated socioeconomic conditions and weakened the health system, complicating the management of COVID-19 pandemic, especially for cancer patients who are doubly-at risk. Augusta Victoria Hospital (AVH) is Palestine’s only specialized cancer hospital, receiving patients from the Gaza Strip and the West Bank for oncology, nephrology, hematology, and radiotherapy. AVH’s preparedness measures enabled its agile response. These proactive and innovative preparedness measures included: implementing a facility-level preparedness and response plan; utilizing multidisciplinary team-based and evidence-informed approaches to decision making; prioritizing health workers’ safety and education; establishing in-house PCR testing to scale up timely screenings; and accommodating health workers, patients, and their relatives at hospital hotels, to maintain daily, continuous and critical health care for cancer patients and limit the spread of infection. At the facility-level, the biggest challenge faced by AVH was continuing essential and daily care for immunocompromised patients while protecting them from potential infection from relatives, hospital staff and other suspected patients. At the national level, the lack of preparedness, inequalities in vaccine distribution, political instability, violence, delays in obtaining medical exit permits to reach Jerusalem, weakened AVH’s response. AVH’s flexible financing, hospital accreditation, and strong leadership and coordination enabled its agility and resilience. Despite compiling challenges, the hospital’s proactive and innovative interventions minimized the risk of infection among two high-risk groups: the immunocompromised patients and their health workers, providing invaluable lessons for health facilities in other fragile-and-conflict-affected settings.